2022
DOI: 10.1371/journal.pone.0264955
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness, knowledge of availability, and willingness to use neurosurgical care services in Sub-Saharan Africa: A cross-sectional study

Abstract: Introduction Low- and middle-income countries bear the majority of neurosurgical disease burden and patients face significant barriers to seeking, reaching, and receiving care. We aimed to understand barriers to seeking care among adult Africans by evaluating the public perception, knowledge of availability, and readiness to use neurosurgical care services. Methods An e-survey was distributed among African adults who are not in the health sector or pursuing a health-related degree. Chi-square test and ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It can be concluded that most medical travels are due to low cost and high quality of services. 20 A study in Nigeria by Idowu and Fatai Adeniyi indicated that governments in different countries should have laws to ensure that medical tourists receive proper care and followup treatment. 21 In South Africa, Makinde reported that the increase in the use of the Internet and social media, the existence of a legal framework, the improved laws of medical tourism agencies, and skilled human resources were among the factors that improved the medical tourism status.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that most medical travels are due to low cost and high quality of services. 20 A study in Nigeria by Idowu and Fatai Adeniyi indicated that governments in different countries should have laws to ensure that medical tourists receive proper care and followup treatment. 21 In South Africa, Makinde reported that the increase in the use of the Internet and social media, the existence of a legal framework, the improved laws of medical tourism agencies, and skilled human resources were among the factors that improved the medical tourism status.…”
Section: Discussionmentioning
confidence: 99%